The Role and Regulation of Sox9 in the Human Hair Follicle and Basal Cell Carcinoma. - Reeves, Andrew. (2017)
Abstract: Constitutively activating mutations in the Sonic Hedgehog pathway are the drivers of basal cell carcinoma (BCC). However, while these mutations may be the initial driver of tumor formation it has more recently been established that without Wnt/β-catenin signaling the Shh mutations cannot lead to tumor formation. The transcription factor Sox9 is a target of both Shh and Wnt signaling and has been implicated in progression and aggressiveness in many different types of tumors. BCC tumors and hair follicles express many of the same genes, including Sox9, and are therefore thought to follow similar developmental pathways. Sox9, in particular, is necessary for the development of the hair follicle stem cell niche and maintenance of hair growth, without it the pool of proliferative cells is exhausted and the hair follicle can no longer grow. Though critical for hair follicle stem cells, Sox9 has not been studied in BCC. Therefore, both primary hair follicle outer root sheath (ORS) keratinocytes and BCC cells were used to study the role and regulation of Sox9 to better understand their differences and potentially find new therapeutic targets. Using RNAi knockdown techniques, Sox9 was found to be a key regulator of proliferation and self-renewal in both ORS-derived keratinocytes and BCC cells. The regulation of Sox9 by β-catenin, however, was reversed in the two cell types. β-catenin positively regulated Sox9 in the BCC cells whereas activation of β-catenin nuclear translocation caused a loss of Sox9 expression in the ORS keratinocytes. Fhit, a known β-catenin nuclear repressor, was found to partially mediate the down-regulation of Sox9 in the ORS cells. Chromatin immunoprecipitation (ChIP) showed that upon inhibition of GSK-3β, Fhit was enriched at the transcription start site of Sox9 along with β-catenin in ORS cells. Similarly, knockdown of Fhit in BCC cells resulted in increased Sox9 expression indicating that Fhit acts as a repressor of β-catenin mediated Sox9 expression in BCC cells. Furthermore, Fhit knockdown increased the invasiveness of BCC cells through a Matrigel invasion chamber, indicating that a loss of Fhit may be a biomarker of infiltrative BCC. Notch1 was also found to positively regulate Sox9 in the ORS but negatively regulated Sox9 in the BCC cells. In the ORS cells, GSK-3β inhibition led to the loss of Notch1 DNA binding upstream of Sox9 and decreased Sox9 expression. I conclude that Notch1 drives Sox9 expression in ORS keratinocytes and activation of β-catenin disrupts Notch and recruits Fhit to repress Sox9 expression. In BCC, activation of β-catenin drives Sox9 though unknown mediators, and through a loss of Fhit. In parallel with the hair follicle and BCC work, I generated biomaterials using silk fibroin to modulate macrophage differentiation both in vitro and in vivo. Macrophages are involved in many diseases ranging from metabolic disease to atherosclerosis and cancer. In each disease, and during normal wound healing, macrophages are represented as either of two general phenotypes: M1, inflammatory macrophages or M2 tissue-regenerative macrophages. Silk biomaterials were chosen to deliver cytokines to macrophages to force them to polarize into either M1 or M2 depending on the desired outcome. To this end, silk films were created with varying thicknesses and crystallization times to optimize the release profiles of IFN-gamma or IL-4 for M1 or M2 macrophage polarization, respectively. Low molecular weight silk films, with minimal crystallization showed the best release profile and were able to polarize the THP-1 derived macrophage. In vivo, silk films containing IL-4 had the largest effect but did not polarize all macrophage strictly to M2 as there were many M1 macrophage as well, indicating that more work needs to be done to optimize the films for in vivo studies.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: David Kaplan.; Committee: James Schwob, Brent Cochran, Jonathan Garlick, Gary Rogers, and Bruce Morgan.; Keywords: Cellular biology, Physiology, and Oncology.